Antimicrobial Coating Efficacy for Prevention of Pseudomonas aeruginosa Biofilm Growth on ISS Water System Materials - Mettler, Madelyn K.; Parker, Ceth W.; Venkateswaran, Kasthuri; Peyton, Brent M. (Frontiers in Microbiology, 2022)
Biofilms can lead to biofouling, microbially induced corrosion, physical impediment and eventual loss in function of water systems and other engineered systems. The remoteness and closed environment of the International Space Station (ISS) makes it vulnerable to unchecked biofilm growth; thus, biofilm mitigation strategies are crucial for current ISS operation and future long duration and deep space crewed missions. In this study, a space flown bacterial strain of Pseudomonas aeruginosa (PA14) was used as a model organism for its ability to form biofilms. Additionally, a novel antimicrobial coating’s ability to reduce biofilm accumulation on stainless steel, Teflon, titanium, and Inconel (all used in the ISS water treatment and handling systems) was analyzed. Coated materials demonstrated reductions of P. aeruginosa biofilm across all materials when tested in a continuous flow system with tryptic soy broth medium. However, the coating lost efficacy in potato dextrose broth medium. These findings were corroborated via scanning electron microscopy (SEM). This study illustrates the fundamental importance of using multiple approaches to test antibiofilm strategies, as well as the specificity in which conditions such strategies can be implemented.